2019
DOI: 10.1242/jeb.176263
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding topsy-turvy: how Anna's hummingbirds (Calypte anna) fly through upward gusts

Abstract: Flying organisms frequently confront the challenge of maintaining stability when moving within highly dynamic airflows near the Earth's surface. Either aerodynamic or inertial forces generated by appendages and other structures, such as the tail, may be used to offset aerial perturbations, but these responses have not been well characterized. To better understand how hummingbirds modify wing and tail motions in response to individual gusts, we filmed Anna's hummingbirds as they negotiated an upward jet of fast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…For example, as a hiker navigates rough terrain, each step requires adjustments of foot placement, stance duration, and force generation to maintain stability and to progress. As a hummingbird encounters a gust of wind, it makes rapid corrections to recover stable flight (Badger et al, 2019). Food oral processing involves instantto-instant decision making about chewing, bolus molding, and transport for swallowing that depend on the changing mechanical properties of food (Chen, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…For example, as a hiker navigates rough terrain, each step requires adjustments of foot placement, stance duration, and force generation to maintain stability and to progress. As a hummingbird encounters a gust of wind, it makes rapid corrections to recover stable flight (Badger et al, 2019). Food oral processing involves instantto-instant decision making about chewing, bolus molding, and transport for swallowing that depend on the changing mechanical properties of food (Chen, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Birds may cope with gusts in a similar way, but the response times and dynamics by which they deal with aerodynamic perturbations are not known, as simultaneous measurements of both the bird's kinematics and the properties of the unsteady airflows they encounter are required. Most previous studies of bird flight mechanics (but see [8]) have taken place in steady laboratory conditions, such as corridors [9][10][11], or wind tunnels [12][13][14][15][16][17], or outdoors [18][19][20][21], where the moment-to-moment variation in the wind that the birds encountered could not be quantified.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29][30][31][32][33] Nakata et al 34 showed that flexible flapping wings can be beneficial for longitudinal gust mitigation. Badger et al 35 found that the use of a deflectable tail on a glider model can enhance the stability of Anna's hummingbirds flying into a vertical gust. Jakobi et al 36 studied the effects of gusts impinging from different directions on bumblebees and found that bees can mitigate the gust influence by using different maneuvering strategies.…”
Section: Introductionmentioning
confidence: 99%